Use of technology application by destination operator / Kim Kyung Joo, Nur Afza Azman, Nur Alya Athirah Madzlaan and Nur Maisarah Saiful Nizam - Kim, Kyung Joo; Azman, Nur Afza; Madzlaan, Nur Alya Athirah; Saiful Nizam, Nur Maisarah (2022)
Covid-19 struck the world and nothing has remained the same. The various industries of the world can attest to how much effect the abrupt disruption amounted to their various sectors and how much it affected them especially in destination operator. The research objective is to create a service that can be used in destination operator that are affected by the Covid-19 in their daily promotion with using the knowledge IT and to discuss technological solutions for better tourism. The research problem is how technological development affect destination operator that leading to innovation contribution to the industry. So, we decide to use a tool which is intro travel app to develop destination operator. It is because this app concludes all the information about the trip and we just need to refer this app if we have a problem with our trip.